Feminist Futures of Work: Reimagining Labour in the Digital Economy - Payal Arora; Usha Raman; René König (Amsterdam University Press, 2023)
The future of work is at the centre of debates related to the emerging digital society. Concerns range from the inclusion, equity, and dignity of those at the far end of the value chain, who participate on and off platforms, often in the shadows, invisible to policymakers, designers, and consumers. Precarity and informality characterize this largely female workforce, across sectors ranging from artisanal work to salon services to ride hailing and construction. A feminist reimagining of the futures of work—what we term as "FemWork" —is the need of the day and should manifest in multiple and various forms, placing the worker at the core and drawing on her experiences, aspirations, and realities. This volume offers grounded insights from academic, activist, legal, development and design perspectives that can help us think through these inclusive futures and possibly create digital, social, and governance infrastructures of work that are fairer and more meaningful.
Keywords: 330; Future of Work; Global South; Digitization; Feminism; Informal Labour